The Dynamics Of Value Creation : The Case of the Surinamese Government - Hoff, Maarten C. (Advances in Social Sciences Research Journal, 2019)
The purpose of this paper is to demonstrate the time dependent value creation by the Surinamese government. There is a significant discrepancy between what the political leadership promises and plans, and what is realized. What matters first is not competitive advantage of the nation, but the creation of value. Based on the idea of the dynamic management performance concept, a thorough study of primary and secondary sources was conducted within the context of how value creation develops by strategy and innovation. The drivers behind this process are public governance and both, human and social capital. The most essential finding is that the governing political leadership heads the country downward into an unhealthy socio-economic system. Although, not yet well developed, both human capital as well as social capital must have the priority in order to safeguard the country from a serious existential crisis. This paper may to contribute to a triple loop learning process related to value creation (the return on strategy).